Primitive Adapidae from Namibia sheds light on the early primate radiation in Africa - (:unkn) unknown (My University, 2018)
The initial radiation of primates is best documented on Northern continents, in which two groups are abundant and well-known : the Omomyiformes, often considered to be primitive haplorhines, and the Adapiformes, usually considered to be strepsirrhines. The extinct Adapidae is one of the families of the Adapiformes, which was first documented in Europe and more recently found in Asia and North Africa. The late Eocene African adapids, from the Egyptian Fayum deposits, appear as a group of three genera constituting with the European genus Caenopithecus, a monophyletic subfamily, the Caenopithecinae, sister group to the otherwise exclusively European Adapinae. We report here the discovery, in the Middle Eocene locality of Black Crow in Namibia, of an undoubted primitive adapid, Namadapis interdictus nov. gen. nov. sp., which compares closely with the European genus Microadapis and the Chinese genus Adapoides. It also appears smaller, more primitive, closely related to the Fayum caenopithecines, being broadly ancestral to them but not directly in line with the three genera. The three primitive middle Eocene adapid genera present in Europe, Asia and Africa lead us to recognize an early differentiation between European Adapinae and African Caenopithecinae, the latter becoming more cristodont at smaller size than the former. A dispersal of an early adapid to Africa is confirmed, however we suggest an Asiatic instead of a European origin for the colonizer. The new Namibian fossil provides clues to interpret the enigmatic Notnamaia found in the same locality : it is probably an adapid. These two forms contrast with the late early or early middle Eocene primates recorded in North Africa, documenting an unsuspected degree of diversity and endemism within middle Eocene African primates. A new look at two poorly known late Eocene primates from the same region in Namibia allows the recognition of a proteopithecid and emphasizes the distinctiveness of the lemuriform.
Keywords: African Research